Factors Affecting the Competitiveness of Indonesian Cocoa Exports - Ninin Eva Andika Rada; I Wayan Sukadana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Competitiveness is the economic ability of a country to innovate, increase productivity, and maintain its position in the global market. Competitiveness is one of the most important activities for the development of the Indonesian economy, high competitiveness helps countries to adapt to global changes, improve the welfare of their people, and achieve sustainable economic growth. International trade is a trading activity carried out by the people of a country with the people of another country on the basis of mutual agreement. Trading activities are activities related to transactions of goods and services domestically and between countries with the aim of gaining profit. With the advancement and development of technology, in the future, international economic and trade activities will also increase. This international trade occurs because a country is unable to meet its needs, this encourages a country to trade. International trade consists of export and import activities. Export is the activity of removing goods from the Indonesian customs area and services from the territory of the Republic of Indonesia. The customs area is the territory of the Republic of Indonesia which includes land, waters, airspace above it, and certain places in the exclusive economic zone and continental shelf. Cocoa is one of Indonesia's leading export commodities. Cocoa commodities consistently act as a source of foreign exchange that contributes to the structure of the Indonesian economy. This study aims to analyze competitiveness, the influence of production, and international prices on the competitiveness of Indonesian cocoa exports. The data used in the study are secondary time series data from 1990 to 2023. The analysis used in this study is Relevant Comparative Advantage (RCA) and multiple linear regression. Based on the results of the Relevant Comparative Advantage (RCA) analysis, the RCA value is greater than 1, indicating that Indonesian cocoa exports have strong competitiveness. Based on the results of multiple linear analysis, it shows that production does not have a significant effect on the competitiveness of cocoa exports, international prices have a positive and significant effect on the competitiveness of cocoa.